The Effectiveness of Implementing a Complete Systematic Land Registration (PTSL) Policy in Realizing Legal Certainty for Rightsholders - Rahmanto, Endy Satya; Mashdurohatun, Anis (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
The purpose of the implementation of registration and issuance of land certificates as stated inGovernment Regulation Number 18 of 2021 concerning Management Rights, Land Rights, Flats Units, and Land Registration.is a manifestation of the purpose of land registration itself and one of the products is a certificate of land rights.The PTSL program is a land registration activity that is carried out simultaneously which covers all land registration objects that have not been registered in one village area or other names.The existence of the PTSL program indirectly provides legal protection to the community in owning land rights because mprotect the actual holder or owner of land rights and there is no guarantee from the government regarding the correctness of juridical data and physical data listed in the land book register or land certificate. Research objectives namely to find out and analyze the implementation of PTSL policies and the effectiveness of the PTSL program in realizing legal certainty for rights holders in the Lamongan Regency area. From the research carried out, it can be concluded that the PTSL of the District Land Office was carried out in several stages, namely: preparation, counseling, data collection and processing of juridical data processing, land inspection, announcement of physical data, validation of physical data, issuance of decisions on granting land rights, bookkeeping of rights over land, issuance and submission of certificates, document management, and reporting.Effectivenessthe implementation of the PTSL policy and its solutions are explained at several points, namely: 1)That the PTSL program has been effective can be seen from the objectives to be achieved through the PTSL program. This is also supported by the important role of several related parties such as the National Land Agency, the subdistrict, the village head and the head of the environment; 2) The PTSL program has been successfully implemented in Bluluk and Kedungpring Districts. The PTSL activity was successful because of the community's enthusiasm for the free land registration program and the 100% completion, namely 2,500 certificates; 3) The PTSL program already has simple facilities and infrastructure that support the success of this program such as a hall as a temporary post for the BPN and tables and chairs; 4) The program has been implemented in accordance with the plan, namely with evidence that the program has been implemented according to plan, namely the presence of BPN officers who are at the command post,Keywords: Certainty; Rights; Holders.